KOLABORASI FISH-NET DAN TECHNOLOGY UNTUK OPTIMALISASI ALAT TANGKAP IKAN - Irwan, Irwan; Fikar, Sul; Surachmad, Winarto; Hayati, Lilis Nur (ILKOM Jurnal Ilmiah, 2018)
AbstractKelurahan Untia is one of the areas occupied by the fishermen and also the majority of the population work as fishermen catch fishermen. The dominant fishing gear used by fishermen in the village of Untia is surface gill net. But the use of surface gill net capture device is considered not effective and efficient because it has constraints on the process of checking the net, the old fishing process, the net tends to disappear, and the catch is considered less. So from that problem, we encourage us to create a technological innovation called FiNe-Tech (Fish Net Technology). FiNe-Tech is designed to be able to monitor fish trapped in surface gill net captures, simplify the process of catching fish in the sea, tracking the position of the jarring, speeding up the fishing process, and increasing the net catch through a smartphone application at close range and distance from the position nets even though we are at home though.